IDENTIFYING PARTNER COUNTRY’S IN GLOBAL INNOVATION OUTPUT INDEX INDICATORS: A MULTIVARIATE APPROACH - Rabia, Maria Danesa S. (International Journal of Psychosocial Rehabilitation, 2020)
One of the significant indicators of the country’s development is having the presence of quality, and innovative outputs come from different sectors. This study examined the recent global innovation output index of 129 countries by employing factor analysis and non-hierarchical cluster analysis to construct factors and identify partners. Resulted to Eight common factors using the factor loadings and scree plot of 35 indicators. The factors differ substantially from the indicators used in previous data and also lead to different rankings of countries. As rankings are not that informative without further information, the distance between each country and the sample mean were considered and analyzed. Differences between countries are much more pronounced for the factors identified in the global innovation index than for individual country indicators. In the non-hierarchical method cluster analysis, the classification of the countries generated seven homogenous groups and was enhanced using multiple regression analysis to identify the predictors of the 2019 Index of Economic Freedom (IEF).